MODEL SISTIM INFORMASI GEOGRAFIS UNTUK ESTIMASI VOLUME ALIRAN DAN EROSI SEDIMEN DI DAS RIAM KANAN PROVINSI KALIMANTAN SELATAN - Abdur Rahman; Dini Sofarini (Fish Scientiae, 2019)
In determining the estimated volume flow, required an appropriate model toestimate the value of the volume flow of a watershed. It has been a decline in the carrying capacity of the Sub Watershed of Riam Kanan as the catchment area due to critical land cover. This study aims to estimate the flow of volume and its distribution in the Riam Kanan Watershed based on data Landsat7 ETM + Satellite Imagery.The results yield a regression equation Qp = 0.007p + 56.85 regression rate of 89.6%, indicating that land cover can lead directly to changes in flow volume in the sub watershed of Riam Kanan By using the data flow volume recorded on board thought the water reservoir (DMA) and data rains cause, the lowest flow volume data obtained in the lowest in Rantau Balai amount of 2.14 m3/sec and the highest in the Rantau Bujur amount of 17.65 m3/sec. As for the areas Bunglai, Tiwingan, Kalaan and Belangian have moderate flow volume ranged from 2.16 m3/sec - 6.59 m3/sec.